Handbook of research on Web information systems quality - Calero, Coral, 1968-; Moraga, Ma. Angeles (Maria Angeles); Piattini, Mario, 1966- (Information Science Reference, 2008)
"This book integrates invaluable research on the models, measures, and methodologies of Web information systems, software quality, and Web engineering into one practical guide to Web information systems quality, making this handbook of research an essential addition to all library collections"--Provided by publisher.